reconhub/incidence: Incidence version 1.5.3 - Jombart,T; Kamvar,Z; Cai,J; Chisholm,S; Fitzjohn,R; Schumacher,J; Bhatia,S (2018)
This is a patch release that fixes an issue with handling single-group incidence curves.You can install this version like so:remotes::install_github("reconhub/incidence@1.5.3")